INTERNALISASI KARAKTER MELALUI PENDIDIKAN ISLAM PADA PENDIDIKAN DASAR ANAK - M.Pd, Toni Nasution (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Abstract: Character becomes a reflection of education in basic education of children, so that characters that tend to be able to become role models and intact personalities as a true example are taken care of and developed in the concept of children's basic education. In line with this, Islamic education is a guide for future generations of children as adherents of the Islamic faith as a religion that is haq for every Muslim. This means that Islamic education in basic education should be instilled early on so that through Islamic education students are able to know themselves and their gods and their rights and obligations to become personal characters, competent, and responsible. For this reason, the existence of this article is able to open up the discourse of thinking we see the moral and character damage of today's children. That the facts in the field show that it is easier for children to understand briefly about mobile / Gagget than to be honest in their daily lives. This is a matter of character that must be considered in the world of Islamic education. Through Islamic education the characters are instilled so that they are able to be independent, honest and devoted. Key Word: Character, Islamic Education and Basic Education Abstrak: Karakter menjadi cerminan pendidikan dalam pendidikan dasar anak, sehingga dengan karakter yang cenderung mampu menjadi tauladan dan kepribadian yang utuh sebagai contoh sejatinya di jaga serta ditumbuh kembangkan dalam konsep pendidikan dasar anak. Sejalan dengan hal tersebut bahwa pendidikan islam menjadi jalan petunjuk bagi generasi masa depan anak sebagai penganut kepercayaan Islam sebagai agama yang haq bagi setiap muslim. Artinya bahwa pendidikan islam pada pendidikan dasar sejak dini sudah seharusnya di tanamkan sehingga melalui pendidikan islam tersebut siswa mampu mengenal dirinya dan tuhannya serta hak dan kewajibannya agar menjadi pribadi yang berkarakter, kompeten, dan bertanggungjawab. Untuk itu dengan adanya tulisan ini mampu membuka wacana berpikir kita melihat rusaknya moral dan karakter anak-anak masa kini. Bahwa fakta dilapangan menunjukkan anak-anak lebih mudah memaha secara singkat mobile/Gagget dari pada berlaku jujur dalam kehidupan sehari-hari. Hal tersebut menjadi persoalan karakter yang harus di perhatikan dalam dunia pendidikan islam. Melalui pendidikan Islam karakter di tanamkan sehingga mampu mandiri, jujur dan bertaqwa. Kata Kunci: Karakter, Pendidikan Islam dan Pendidikan Dasar